Thimbleberry stories - Rylant, Cynthia (Harcourt Brace, 2000)
Nigel Chipmunk shares a pleasant life with his friends Dipper the hummingbird, Little Owl, Copper the butterfly, Claudius the garter snake, and Mudpuppy the salamander.